Convenient Disposal: Posadas County Mysteries #3 - Havill, Steven (Scottsdale, AZ : Poisoned Pen Press, 2010)
Undersheriff Estelle Reyes-Guzman is called in to investigate a scene of domestic violence, but she becomes suspicious of an outside assailant when the family's next-door neighbor disappears.7.
New Book Winter 2024.
Keywords: Reyes-Guzman, Estelle (Fictitious character) -- Fiction; High school students -- Fiction -- Crimes against; Missing persons -- Fiction; Sheriffs -- Fiction; New Mexico -- Fiction; Mystery fiction